Property rights, taxpayer rights, and the multiscalar attack on the State: Consequences for regionalism in the United States - Christopher Niedt; Margaret Weir (University of California, Institute of Urban and Regional Development (IURD), 2007)
Studies of new regionalism often focus on the new actors or goals characteristic of contemporary regional coalitions, at the cost of recognizing how competing social movements may constrain regional policy. This paper considers the recent evolution of the property rights and taxpayer movements in the U.S., and how their attacks on state regulatory and tax capacity have affected regional governance. The development and strategic use of scalar repertoires and framing strategies has enabled these movements to take advantage of political opportunities at different scales. Regionalists have been slow to build the versatile scalar repertoires needed to respond to these challenges.
Keywords: 330